A patra grație. Genius corpus sau prezența absentă a instanței creatoare - Man, Ioana (Dialogoi. Rivista di studi comparatistici, 2020)
The fourth grace. Genius corpus or the absent presence of the creative instance introduces the diversity and complexity of the presence of bodies in the material and immaterial culture of a present that is a reflection of a past that is no longer capable of dictating the law, but is not yet completely overcome and even more than canceled. And this is so true if we think of a millennial past, such as that interpreted by the great ancient religions, such as classical mythologies or by the most recent. On the other hand, the awareness of bodies, living or natural, but also solùid and very old, does not differ from the elements of the structure of the Cosmos or of the planet Earth. However, it emerges as a result of the twentieth century, in the effort to overcome spatial dimensions, traditionally made understandable by the flat projection (long / wide) in the projection of heights, in skyscrapers, the premise of virtual spaces.